Clinical Comparison of Preterm Birth and Spontaneous Preterm Birth in Severe Preeclampsia. (15th September 2022) - Wen, Yanqing; Yang, Xiaoyan
Abstract : Severe preeclampsia is accompanied by many complications, which is extremely harmful to pregnant women and fetuses. However, in the classification of preterm birth, it is generally divided into spontaneous preterm birth and therapeutic preterm birth, and insufficient attention has been paid to preterm birth in severe preeclampsia. This article aims to explore the clinical difference between preterm birth in severe preeclampsia and spontaneous preterm birth. In the experiment, this paper selected pregnant women who delivered and were treated in a hospital from April 2010 to April 2020 as cases. In terms of grouping, not only are they divided into severe eclampsia group (observation group 1), spontaneous preterm birth group (observation group 2), and general delivery group (control group) according to the cause of premature birth, but also according to the gestational age of severe eclampsia onset, preterm weeks, and other groups. Not only the clinical difference between severe preeclampsia preterm birth and spontaneous preterm birth was compared horizontally, but also the factors affecting the complications of preterm pregnant women, perinatal asphyxia rate, and mortality were longitudinally analyzed. The experimental results in this paper showed that there were significant differences in maternal complications and neonatal mortality between the severe preeclampsia preterm group and the spontaneous preterm group (P < 0.05). In addition, the severe preeclampsia preterm birth group was more harmful than the spontaneous preterm birth group. The complication rate of the severe preeclampsia preterm birth group was 10% higher than that of the spontaneous preterm birth group, and the neonatal mortality rate was 2% higher.